PENGARUH KARAKTERISTIK INDIVIDU DAN PELATIHAN TERHADAP PRESTASI KERJA PEGAWAI PADA BAGIAN KEUANGAN KABUPATEN KUTAI TIMUR - Nur Rachim; Aji Ratna Kusuma; Sutadji . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The main issue raised in this study is wheter or not individual characteristics and education & training could together and partially have significant effect on the performance of employees in the Finance Department Secretariat of the East Kutai Regency and among these varaiabel, which variables are the dominant influence on the performance of employees in the Finance Department Secretariat of the East Kutai Regency.